DESAIN MEDIA PEMBELAJARAN BERBASIS E MODUL PADA MATERI LOGIKA MATEMATIKA - Lailatul Lutfiyah; Achmad Buchori; Intan Indiati (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This research is development research that designs products in the form of e-module mathematics for class XI SMA/SMK/MA. This research is focused on the feasibility of the product developed by involving validation from media experts and material experts. The purpose of this research is to develop teaching modules for students in the form of e-modules with mathematical logic material using the 4D model, namely. definition, design, development and dissemination phases. In this study, the development procedure was carried out up to the develop stage because the time for making and validating the product was limited. Data collection techniques were carried out using observation sheets consisting of media expert observation sheets and material expert observation sheets. The data analysis technique refers to the Likert scale and the results are described qualitatively. This mathematical logic e-module was first validated by media and materials experts as well as a student survey. The average percentage of the material expert's assessment was 87.5%, the percentage of the media expert's assessment was 86.8%, and the percentage of the student's conformity assessment was 86.2%, which means that the media from the e-module can be used in a very good category. Thus, this mathematical logic e-module product can be used in mathematics-logic material and can be utilized in teaching mathematics for class XI SMK